Can Long-Term Regular Practice of Physical Exercises Including Taichi Improve Finger Tapping of Patients Presenting With Mild Cognitive Impairment? - Zhang, Lingli; Zhao, Yilong; Shen, Chao; Lei, Le; Dong, Junjie; Zou, Dongchen; Zou, Jun; Wang, Miao (Frontiers in Physiology, 2018)
Background: Mild cognitive impairment (MCI) is a brain disease with both anatomical and functional alterations. There is clear evidence that individuals that are diagnosed with MCI have a high risk to develop dementia in the next 2-5 years compared to an age-matched population with a non-MCI diagnosis. The present study aimed to investigate whether the finger tapping frequency of patients with MCI was different from that of healthy individuals without MCI, and whether Tai Chi, a traditional Chinese movement discipline, could improve the finger tapping frequency of MCI patients. Methods: The study population consisted of subjects of ≥50 years of age. Group one included 40 subjects without exercise habits from communities of Yangpu District in Shanghai, and group two included 60 subjects from a Tai Chi class in Shanghai Elderly University of Huangpu District. The Montreal Cognitive Assessment (MoCA) and a finger tapping test were conducted to assess the finger tapping frequency of all subjects. Results: The MoCA score of MCI subjects was significantly lower compared to subjects without MCI (P<0.01), and was not influenced by age, weight or height. The finger tapping frequency of MCI subjects’ left hands was significantly lower compared to that of healthy subjects without MCI (P<0.01), and a similar trend was observed for the subjects’ right hand. The MoCA score of MCI subjects in the Tai Chi class was significantly lower than that of healthy subjects without MCI (P<0.01), which was not influenced by age, weight or height. The finger tapping frequency of MCI subjects’ right hands was lower compared to that of healthy subjects in the Tai Chi class without MCI (P<0.05), but no significant difference regarding the finger tapping frequency of the left hand was observed. Conclusion: These findings suggested that finger tapping frequency of MCI subjects was significantly lower compared to normal subjects without MCI, and long-term Tai Chi exercise could reduce this significant difference. Moreover, there was no significant difference between groups for the subjects’ non-dominant (left) hand.